The Impossibility of a Future in the Absence of a Past: Drifting in the In-Between - Boon, Sonja; Lahey, Kate (Atlantis)

(untitled) (Mount Saint Vincent University, 2019)
In this collaborative paper, we bring the work of Billy-Ray Belcourt, Leanne Betasamosake Simpson, Dionne Brand, and M. NourbeSe Philip into conversation in order to consider the concept of drift. Drawing on drift as both metaphor and methodology, we argue that drifting is not aimless or passive, as dictionary definitions suggest; rather, as a form of refusal, to follow the work of Eve Tuck and K. Wayne Yang (2014a, 2014b), it can be understood as resistance to colonial gestures of capture and containment. Inherently mobile, drift revels in inadvertent assemblages and volatile juxtapositions that reveal the artifice of the worlds we currently inhabit, in the process making new worlds possible. In this way, we suggest that drift is necessarily decolonial, in that it is premised on different ways of interacting among human, non-human, and more-than-human. Working through themes of intimacy, love, origins, dirt, and accountings, we argue that drift can be more productively read as an agential mode of kinning, making, and thinking together.